Risk factors of Gestational Trofoblastic Disease. Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2020)
Gestational Trophoblastic Disease (TSG) is a pathology of the first half of pregnancy characterized by a hydropic degeneration of the chorionic villi that spans the placenta and the rest of the ovular complex; it is usually benign, but it can become malignant and spread to other tissues. A descriptive transversal study with retrospective review of medical charts was performed in order to determine the risk factors for TSG of patients evaluated at the Servicio de Emergencia Gineco-Obstétrica of the Hospital Dr. Antonio Maria Pineda during the January-August 2018 period. Fifty-five medical charts were reviewed. Results show that TSG was more common in women < 28 years old that lived in urban areas, which had several pregnancies, with no prior history of spontaneous abortion, molar pregnancy, use of intrauterine devices or prolonged use of contraceptive pills. In conclusion, a follow-up of young pregnant women is necessary in order to have an on time diagnosis of this disease as well as promote measures that guarantee the patients’ health as well as her life.
Keywords: gestational trophoblastic disease; risk factors; abortion; intrauterine devices